Dampak Penerapan Profil Pelajar Pancasila Dimensi Beriman, Bertakwa Kepada Tuhan Yang Maha Esa dan Berakhlak Mulia di SMP Nihayatul Amal Rawamerta Karawang - Fikhria, Ratu; Rukajat, Ajat; Susanto, Agus (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this article is to provide an overview or situation about the impact of the application of the Pancasila student profile on this dimension at Nihayatul Amal Rawamerta Karawang Junior High School. This study uses a qualitative approach with a descriptive method. The data collection method is by observation, interviews, and documentation. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the sympathy of faith is the recognition of verbal pronunciation of the truth that is special and believes it in the heart and then applies it in oneself. The dimension of fearing Allah SWT is to protect oneself from wrath by carrying out all His commands and staying away from all His prohibitions. The dimension of noble character is to do good deeds with sincerity without expecting praise from others. It is hoped that the positive impact of the implementation of the Pancasila student profile in the dimension of faith, fear of God Almighty, and noble character at Nihayatul Amal Rawamerta Karawang Junior High School will form students who have a strong character, are ethical, and play an active role in the usefulness of community life